NEW EXPERIMENTS IN CLASSICAL DANCES: शास्त्रीय नृत्यों में नवीन प्रयोग - Srivastava, Monika (International Journal of Research -GRANTHAALAYAH, 2015)
The feeling of unification with God is the creativity of classical dances. It is an expression of feeling, but emotion - of eternal, eternal values, of Satyam Shivam and beauty. Truth, beauty is born from the eternal realization of Siva. The body and mind bind with beauty, and this door is made with the beauty of art. Suष्टुu became beautiful with Nara: meaning sun. With this, the expressions of sad, gentle, pleasant, delightful, charu, shobhan, rachir and auspicious. Beauty is a toxic form. This concept is the legislation of Indian aesthetics and the Western aestheticians interpret its form in this way - "To understand the true nature of the aesthetics, it is necessary to think only on the word" esthetics ". "It is necessary to have a feeling of joy in artistic beauty. When looking at an artwork, the practitioner must have a feeling of joy in the form combination. परमात्मा से एकाकार होने की भावना ही षास्त्रीय नृत्यों की रचनात्मकता है। वह भावना की अभिव्यक्ति है, लेकिन भावना है- शाष्वत की, शाष्वत मूल्यों की, सत्यम् षिवम् और सौन्दर्य की। सत्य, षिव की शाष्वत् अनुभूति से सौन्दर्य का जन्म होता है। शरीर व मन, सौन्दर्य की डोर से बँधता है और यह डोर कला के सौन्दर्य से निर्मित होती है। सुष्टु नरः अर्थात् सुनरः से सुन्दर बना। इसके साथ उदाŸा, सौम्य, मनोहर, रमणीय, चारू, शोभन, रूचिर व शुभ के भाव जुड़े। सौन्दर्य एक विषुद्ध रूप है। यह अवधारणा भारतीय सौन्दर्यषास्त्रियों का विधान है एवं पाष्चात्य सौन्दर्यषास़्त्री इसके स्वरूप की इस प्रकार व्याख्या करते हैं- ‘‘सौन्दर्यषास्त्र के सच्चे स्वरूप को अच्छी तरह समझने के लिए ‘‘एस्थेटिक्स’’ शब्द पर ही विचार करना आवष्यक है। ‘‘कलात्मक सौन्दर्य में आनन्द की अनुभूति होना आवष्यक है कलाकृति को देखते समय दर्षक को रूप संयोजन में आनन्द की अनुभूति होनी चाहिए।